Theoretical study for the interactions of Coronene-Y interactions by using Density functional theory with hybrid function - Jabbar , Mohammed L. (University of Thi-Qar Journal, 2019)
Molecular geometry and contours have been investigated for Coronene and Coronene-Y molecules throughout the geometrical optimization procedure by using density functional theory (DFT) at 3-21G and B3LYP basis sets. Infrared spectra (IR) demonstrates new bonds belong to Carbon -Y atoms after the interaction. Contours show increasing electrons charges near Y atoms beyond the interaction. Donor and acceptor properties have been studied throughout comparison highest occupied molecular orbital energies of Coronene and individual atoms. Energyband gap for Coronene-P approach to the energy gap of Gallium Arsenide (GaAs). Electronegativity and electrophilicity calculate to the molecules under the study. Dipole moment and polarizability compute. Symmetry shows new point groups after adding Y atoms to Coronene. Density of states diagrams show the anti-ferromagnetic material property for Coronene-S and Coronene-Se. Where Y: refer to atoms (P, S, Se, Zn, Cl, F)